Effects of baker's yeast as a growth promoter supplemented at different levels on growth performance, gut morphology, and carcass characteristics of broiler chickens - Mohamaddin, Nabila; Yaakub, Halimatun; Alimon, Abdul Razak; Samsudin, Anjas Asmara @ Ab Hadi (Malaysian Society of Animal Production, 2017)
A study was performed to determine the effects of varying levels of baker’s yeast supplementation on growing performance, nutrient digestibility, gut morphology, and carcass characteristics of broiler chickens. A total of 200 day-old male Cobb 500 broiler chicks were used and divided equally into 5 dietary treatments: T1 (control), T2 (control + 0.1% baker’s yeast), T3 (control + 0.2% baker’s yeast), T4 (control + 0.4% baker’s yeast), and T5 (control + 0.8% baker’s yeast) with 4 replicates per treatment and 10 birds per replicate. All birds were given the same management and environmental conditions. Significant differences (P<0.05) were observed, with T4 (71.26±0.03 g/d) showed the highest value in weight gain compared to control diet (66.59±0.50 g/d). In FCR, T4 (1.86±0.08) showed the lowest value compared to control diet (2.07±0.08). Also in ileum villus height T4 (1226.1±0.81 μm) showed the highest value compared to control diet (1080.7±0.48 μm). However, no significant difference (P>0.05) was observed for cryptal depth, dry matter and metabolizable energy among all treatments. Meat, bone, and fat ratios recorded significant differences (P<0.05) between dietary treatments and control group. However no significant difference was observed in the dressing percentage among all dietary treatments. The study indicates that dietary supplementation of 0.4% baker’s yeast in the diet increases the growth performance and carcass characteristics, and also improves intestinal morphology and nutrient absorption of broiler chickens.